The trophic role and ecological implications of oval faecal pellets in Terra Nova Bay (Ross Sea) - POVERO, PAOLO; MISIC, CRISTINA; CASTELLANO, MICHELA; FABIANO, MAURO; OSSOLA C. (Polar Biology, 2003)
We studied the role of oval faecal pellets in the carbon-cycle dynamics of the Antarctic coastal area in a laboratory experiment on pellet degradation over time. We observed a rapid increase in the bacterial biomass until 56 h (from 14.73 to 91.09 lgC/l), but a drop to 25.83 lgC/l at the end of the experiment. Dissolved proteins decreased rapidly (from 1,342.7 to 1,177.0 lg/l in the first 32 h) as did nitrate (from 1 to 0.43 lM in the first 56 h), confirming their consumption by microorganisms, but they were observed to increase in the second part of the experiment, up to 1,618.3 lg/l and 17.36 lM for the dissolved proteins and nitrate, respectively. The proteolytic activity increased throughout the incubation from 302.65 nmol/l per hour to 6,641.08 nmol/l per hour, especially in the second half of the experiment. Therefore, we concluded that the microbial community is able to produce, consume and remineralise the available organic substrates and to increase organic-pool quality and inorganic nutrient concentrations dissolved in the overlying water.